Preference and Nutritional Content of Black Wheat Snack Bar with Hibiscus Flavor - Afifah Nurul Hannan; Esteria Priyanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The development of snack bar products using black wheat as the base ingredient and hibiscus flavoring is expected to yield new variations of snack bar products. This study aimed to: Determine the preference levels for the color, aroma, texture, and taste of black wheat snack bars with hibiscus flavor; 2 Determine the carbohydrate, fat, and fiber content of snack bars that are accepted by consumers. The research employed experimental methods, sensory evaluation, and laboratory testing. Three experimental designs were used, involving the addition of hibiscus powder at 5%, 10%, and 15% of the weight of black wheat flour. Data obtained from sensory evaluations were analyzed descriptively, while data from nutritional content test were compared with Recommended Dietary Allowances (RDAs). The research results indicated that the black wheat snack bar with 15% hibiscus powder addition was the most preferred product among the panelists, with 60% of panelists choosing this product. The nutritional content per 30g serving of the black wheat snack bar with hibiscus flavor included 21.9g of carbohydrates, 4.4g of fat, and 1.6g of fiber. Therefore, by consuming this snack bar, 7% of the RDA for carbohydrates, 7% of the RDA for fat, and 5% of the RDA for fiber can be met. In conclusion, this product can be recommended to individuals who want to maintain their health despite frequent snack consumption.